Oscillatory solutions of some autonomous partial differential equations with a parameter - Herrmann, L. (Нелінійні коливання, 2017)
A class of partial differential equations of evolution (stemming from the groundwater flow problems) depending on a parameter τ is studied. The existence of an open interval T⁰ of parameter τ and of a function τ → Θ(τ ), Θ: T⁰ → (0, +∞), is proved with the property that any nonzero global solution u: R⁺ ×Ω → R of the equation cannot remain nonnegative (nonpositive) throughout the set J ×Ω, where J ⊂ R⁺ is any interval the length of which is greater than Θ(τ ). In other words, such solutions are globally oscillatory and Θ(τ ) is the uniform oscillatory time. The interval T⁰ as well as the function Θ are explicitly determined. Вивчається клас еволюцiйних диференцiальних рiвнянь з частинними похiдними iз параметром τ, якi розглядаються в задачах течiї пiдземних вод. Доведено iснування вiдкритого iнтервалу T⁰ параметра τ та функцiї τ → Θ(τ ), Θ: T⁰ → (0, +∞), якi задовольняють таку властивiсть: будь-який ненульовий глобальний розв’язок u: R⁺ × Ω → R рiвняння не може залишатися невiд’ємним (недодатним) на множинi J × Ω, де J ⊂ R⁺ — будь-який iнтервал, довжина якого перевищує Θ(τ ). Iншими словами, такi розв’язки є глобально коливними, а Θ(τ ) — рiвномiрним коливним часом. Iнтервал T⁰ та функцiю Θ знайдено в явному виглядi.